Pyroptosis: the dawn of a new era in endometrial cancer treatment - Peng, Tian; Zhang, Chi; Chen, Wen-Jun; Zhao, Xue-Fei; Wu, Wei-Bo; Yang, Wei-Ji; Liang, Ruo-Jia (Frontiers in Oncology, 2023)
Endometrial cancer (EC) is a malignancy of the inner epithelial lining of the uterus. While early-stage EC is often curable through surgery, the management of advanced, recurrent and metastatic EC poses significant challenges and is associated with a poor prognosis. Pyroptosis, an emerging form of programmed cell death, is characterized by the cleavage of gasdermin proteins, inducing the formation of extensive gasdermin pores in the cell membrane and the leakage of interleukin-1β (IL-1β) and interleukin-18 (IL-18), consequently causing cell swelling, lysis and death. It has been found to be implicated in the occurrence and progression of almost all tumors. Recent studies have demonstrated that regulating tumor cells pyroptosis can exploit synergies function with traditional tumor treatments. This paper provides an overview of the research progress made in molecular mechanisms of pyroptosis. It then discusses the role of pyroptosis and its components in initiation and progression of endometrial cancer, emphasizing recent insights into the underlying mechanisms and highlighting unresolved questions. Furthermore, it explores the potential value of pyroptosis in the treatment of endometrial cancer, considering its current application in tumor radiotherapy, chemotherapy, targeted therapy and immunotherapy.